VARIATION OF CONCENTRATIONS OF SULFATE, METHANESULFONATE AND SULFUR DIOXIDE AT NY-ALESUND IN 1995/96 WINTER - ハラ, ケイイチロウ; オサダ, カズオ; ハヤシ, マサヒコ; マツナガ, カツジ; イワサカ, ヤスノブ; HARA, Keiichiro; OSADA, Kazuo; HAYASHI, Masahiko; MATSUNAGA, Katsuji; IWASAKA, Yasunobu (National Institute of Polar Research, 1997)
P(論文) Atmospheric aerosol particles and sulfur dioxides were collected at Ny-Alesund (78°55′N, 11°56′E) in the winter of 1995/96. The concentrations of water soluble constituents of aerosol particles and gaseous acidic compounds were determined with ion chromatography. High concentrations of sea salts and methanesulfonate were found under warm and humid storm conditions, whereas non sea salt (nss)-SO_4^<2-> and SO_2 showed high concentrations in cold and dry Arctic air masses. Variation of nss-SO_4^<2-> concentrations in mid-December coincided with the variation of SO_2 concentration, but the increase of nss-SO_4^<2-> concentration in early-February lagged behind increase of SO_2 concentration. We discuss this time-lag variation using a simple box model. departmental bulletin paper